Analisis Kestabilan Lereng Pada Rencana Lereng Akhir Penambangan Dengan Tinggi 55 m PT. Atika Tunggal Mandiri, Kecamatan Pangkalan Koto Baru,Sumatera Barat - andre martona risky; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Atika Tunggal Mandiri is a company engaged in the andesite mining business in kabupaten Lima Puluh Kota. In open pit mining, the stability of the mine slope is the most important factor that must be considered in thesustainability of mining activities. The author conducted research at the site of the final mining slope of PT. ATM, with anactual slope height of 13 m and a slope angle of 85°. The final slope of the mine will increase in height, this is due to theexcavation of andesite material to a depth of 55 m. Therefore, it is necessary to review the stability of the slope so that t heslope does not collapse and does not cause losses to the company.In this study, the analysis used is kinematic analysis with dips software and slope stability analysis using the Finite Elementmethod with phase 2 software. which has a landslide potential of 23.37% (Flexural Topling of 12.68% while Direct Toplingof 10.59%). Second, the results of the analysis of the factor of safety (FK) of the slope using the Finite Element method onthe actual slope of 13 m with an angle of 85° are 2.12 (natural condition) and 2.09 (saturated condit ion). Third, to get a safeFK which is 1.30 by making a double bench with a height of 55 m with an overall angle of 65° (the height of the first singleslope is 20 m with an angle of 85° while the second single slope is 35 m with an angle of 65°). FK values obtained are 1.33(natural condition) and 1.31 (saturated condition). Fourth, it is preferable to write a triple bench with a height of 55 m withan overall angle of 70° (the height of the first single slope is 20 m with an angle of 85°, the second single slope is 20 m withan angle of 88° and the third single slope is 15 m with angle of 88°) obtained FK values are 1.35 (natural condition) and 1.33(saturated condition).